A model for comparing sourcing strategies for parts in long life cycle products subject to long-term supply chain disruptions. (1st January 2013) - Prabhakar, Varun J.; Sandborn, Peter
Long life cycle products, commonly found in aviation, medical and critical infrastructure applications, are often fielded and supported for long periods of time (20 years or more). The manufacture and support of these products rely on the availability of suitable parts, which over long periods of time, leaves the parts susceptible to a number of possible supply chain disruptions. This paper presents a methodology to perform trade-off analyses and identify the conditions under which sourcing strategies (with a predetermined number of suppliers) will be cost effective based on the organisation's capability to streamline qualification and support activities. The method utilises a part total cost of ownership approach to identify the life cycle cost trade-offs between extending a part's procurement life through multi-sourcing versus the additional cost of qualifying and supporting the alternative sources. The method is demonstrated for electronic parts in an example case study of linear regulators subject to obsolescence.